Speech Act of Responding to Compliments: A Study of Verbal Politeness Strategies of Spanish and Italians - Garrote, Pilar Robles (Richtmann Publishing, 2012)
This paper aims to provide empirical data relating the verbal politeness strategies used by Italian and Spanishspeakers to one of the speech acts: complimenting. More specifically, the objective of the present study is to classify andcontrast the different resources used in the responses to the compliments analyzed, taking as independent variable thenationality of the participants. The data for the investigation was collected by carrying out a corpus of 400 responses tocompliments obtained from a questionnaire in which 100 Italian and Spanish participants had to react to compliments in variouseveryday situations. Afterwards, the responses were classified according to the different strategies and the percentage of thepresence or absence of the diverse typologies was determined from the answers obtained. The results reveal that both Spanishand Italian informants utilize as a preferential resource the acceptance of the compliment, but it is observed that there are somedifferences in the selection of variants of this superstrategy.